Fabrication of quaternary composite scaffold from silk fibroin, chitosan, gelatin, and alginate for skin regeneration. Issue 44 (12th August 2015) - Sharma, Chhavi; Dinda, Amit K.; Potdar, Pravin D.; Mishra, Narayan C.
ABSTRACT Quaternary composite scaffold consisting of chitosan, alginate, gelatin, and silk fibroin, was fabricated by applying foaming method, for tissue engineering applications. The fabricated scaffold was evaluated for its applicability in skin tissue regeneration. The environmental scanning electron microscopy (ESEM) showed the presence of interconnected pores, mostly spread over the entire surface of the scaffold with mean pore size 92±11.8 μm and the porosity 88%. The scaffold showed good mechanical stability under physiological conditions as determined by short term mechanical stability testing. In vitro scaffold‐degradation study showed no degradation at day 1 and from day 3 scaffold starts degrading. The degradation of the composite scaffold after 28 days was 38%. Less degradation rate of the scaffold might be beneficial, as it can provide sufficient time for the formation of neo‐tissue and extracellular matrix (ECM) during tissue regeneration. In vitro cell culture studies by seeding L929 mouse fibroblast cells over composite scaffold showed good cell viability, proliferation, and adhesion as indicated by 3‐(4, 5‐dimethylthiazol‐2‐yl‐2, 5‐diphenyltetrazolium bromide) (MTT) assay and ESEM of cell‐scaffold construct. Giemsa staining of L929 fibroblast cells over the scaffold showed fibroblastic morphology of L929 cells, having elongated cells with nuclei and faint cytoplasm, and these cells are positive for Oil Red stain and negative for Alizarin Red staining—indicating that they maintained their dermal fibroblastic phenotype and were not differentiated into any other cell types in presence of composite scaffold. Results of histological staining supports growth and viability of L929 fibroblasts over scaffold, thereby proving the great prospective of this scaffold for skin tissue engineering applications. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42743.